Anthraquinone Derivatives in Aqueous Flow Batteries. Issue 8 (14th December 2016) - Gerhardt, Michael R.; Tong, Liuchuan; Gómez‐Bombarelli, Rafael; Chen, Qing; Marshak, Michael P.; Galvin, Cooper J.; Aspuru‐Guzik, Alán; Gordon, Roy G.; Aziz, Michael J.
Abstract : Anthraquinone derivatives are being considered for large scale energy storage applications because of their chemical tunability and rapid redox kinetics. The authors investigate four anthraquinone derivatives as negative electrolyte candidates for an aqueous quinone‐bromide redox flow battery: anthraquinone‐2‐sulfonic acid (AQS), 1, 8‐dihydroxyanthraquinone‐2, 7‐disulfonic acid (DHAQDS), alizarin red S (ARS), and 1, 4‐dihydroxyanthraquinone‐2, 3‐dimethylsulfonic acid (DHAQDMS). The standard reduction potentials are all lower than that of anthraquinone‐2, 7‐disulfonic acid (AQDS), the molecule used in previous quinone‐bromide batteries. DHAQDS and ARS undergo irreversible reactions on contact with bromine, which precludes their use against bromine but not necessarily against other electrolytes. DHAQDMS is apparently unreactive with bromine but cannot be reversibly reduced, whereas AQS is stable against bromine and stable upon reduction. The authors demonstrate an AQS‐bromide flow cell with higher open circuit potential and peak galvanic power density than the equivalent AQDS‐bromide cell. This study demonstrates the use of chemical synthesis to tailor organic molecules for improving flow battery performance. Abstract : Anthraquinones are extremely versatile electroactive species with a vast array of derivative molecules. Anthraquinone derivatives are synthesized and evaluated for use in an aqueous quinone‐bromide redox flow battery. By functionalizing anthraquinone in different ways, its reduction potential can be changed. This approach is used to demonstrate increased voltage in quinone‐bromide flow batteries.